Al-Abnawis and Their Efforts in Preserving the Prophetic Tradition: The Family of Al-Munabbih as a Model - Zekhnini, Sabah Mohammed Abdelrahman (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This research aims to explore Muslim narratives of Al-Abnawis, historically recognized as the People of the Book with Persian roots. Their offspring were referred to as "Al-Abna' " or "Al-Abna'wiyyun” or “sons.” They diligently transmitted hadiths from Prophet Muhammad, including prominent figures like Al-Munabbih, the four brothers, and their descendants. These individuals played a pivotal role in preserving the Sunnah of the Prophet, emphasizing familial transmission in a series spanning from sons to fathers, uncles, and grandfathers. Methods: Employing an inductive approach, the study extrapolated, tracked, and transferred hadiths narrated by the Al-Abnawis. An analytical perspective highlighted their role in safeguarding the Prophet's Sunnah. The statistical method quantified hadiths narrated by Al-Munabbih and his descendants, including Hammam, Wahb, Maqil, and Ghaylan, gaining renown for their narrations in Kutub al-Sitta. Results: The study found that some of Al-Munabbih's brothers were recognized in the Sahihs, while the rest of the family were generally deemed trustworthy. They were acknowledged in the Sunnah and Musnad collections, with hadiths free from Israeli narrations. Additionally, they narrated from various companions (Sahabah) and followers (Tabi’een). Conclusion: Al-Abna'wiyyin play a significant role in preserving the Prophetic traditions. Renowned scholars like Bukhari, Muslim, and Imam Ahmad relied on their narrations. Some contemporaneous with The Prophet’s Companions (Al-Sahabah), they learned directly from them, while later generations from Al-Tabi'een transmitted from prominent hadith scholars. A considerable number of the Abna'wiyyin served as a primary source for narrations in entire regions.